FACTORS THAT INFLUENCE PURCHASE INTENTION CREATIVE ECONOMY PRODUCTS - Hafrizal Okta Ade Putra; Rafi Ridhwan; Yuni Candra (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2023)
This study aims to determine and analyse the effect of price and trust on purchase intention in culinary subsector creative economy products (Kripik Balado Christine Hakim). This research was conducted using descriptive quantitative methods, sampling was carried out by accidental sampling technique, which amounted to 100 respondents. The data analysis techniques used include descriptive analysis, multiple linear regression analysis, t test, F test, and coefficient of determination test. Based on the results of the study, it can be seen that price and trust, both partially and simultaneously, have a positive and significant effect on purchase intention. While the results of the coefficient of determination test show that price and trust contribute to purchase intention by 23.8%.